PENGARUH CITRA MEREK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN AIR MINERAL PADA MEREK RAJA IRODI MAKASSAR - Andi Widiwati; Moh. Rizky Ruslan (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2019)
This research aims to determine which is more dominant of brand image and price to the buying decision thru mineral water on Raja Iro in Makassar. Population in this research is consumer of Raja Iro las 3 years. By using purposive sampling and take a sample as much 102 person or respondents. Meanwhile, data analysis used in this research is multiple linear regression analysis using SPSS IBM Statistics 24. The result of this research indicates that the price is the most dominant have a positive and significant on price to buying decision thru mineral water on Raja Iro brand in Makassar